Comparing two whole task patient simulations for two different dental education topics. (February 2023) - McAlpin, Elizabeth; Levine, Marci; Plass, Jan L.
Abstract: We investigated the effect of two types of whole task patient simulations, role-play and web-based, on learning outcomes for two topics, local anesthesia and non-surgical extractions, in a foundational oral maxillofacial surgery course for second year pre-clinical dental students. Using a 2x2 factorial design, we asked which simulation model allows for deeper cognitive engagement that fosters higher learning outcomes for novices practicing complex skills as a professional, a collaborative role-play simulation ( Role-Play Sim ), or an individually-paced web-based simulation ( Web Sim )? In two studies covering two different topics, we compared the effect of these simulations on 50-item multiple-choice knowledge tests. Participants were randomly assigned to one of four groups: No Sim, Web Sim, Role-Play Sim, or Both Sims . For study 1 covering local anesthesia, there was a statistically significant main effect for the Role-Play Sim, F (1, 105) = 103.804, p  < 0.001, ηp 2  = 0.497, but not for the Web Sim, F (1, 105) = 1.655, p  = 0.201. Similarly, for study 2 covering extractions, there was a statistically significant main effect for the Role-Play Sim, F (1, 108) = 162.362, p  < 0.001, ηp 2  = 0.601, but not for the Web Sim, F (1, 108) = 0.072, p  = 0.798. The interaction term was not statistically significant in either study. Results suggest that role-play simulations achieved a higher level of learning outcomes than the web-based patient simulation. Highlights: 2 studies compared 2 whole task patient simulations: role-play and web-based. Used a 2x2 factorial design and 50-item multiple-choice tests for each study. Study 1 local anesthesia: Role-Play Sim showed statistically significant outcomes . Study 2 extractions: Role-Play Sim showed statistically significant outcomes. Role-Play Sim showed higher learning outcomes compared to Web-Based Sim .